Effects of acacia grades, oil types and preparation methods on the formation and stability of oral emulsions - Boonme,P. (Colegio de Farmaceuticos de la Provincia de Buenos Aires, 2015)
© 2014, Colegio de Farmaceuticos de la Provincia de Buenos Aires. All rights reserved. This study aimed to investigate effects of three parameters, i.e., acacia grades (Acacia BP and spray-dried acacia in original and grinded forms), oil types (mineral oil and castor oil), and preparation methods of primary emulsion (wet gum method and dry gum method), on formation and stability of oral emulsions. It was found that particle aggregation of acacia and high viscosity of oil negatively affected emulsion formation by dry gum method. Wet gum method successfully produced primary emulsions more than dry gum method. The pH values of the obtained emulsions were in the range of 4.56-4.96. All emulsions possessed pseudoplastic flow and their viscosity was similar (p > 0.05). The results of stability test indicated that the studied parameters interferingly influenced on creaming of the emulsions. Storage of the emulsions under freeze-thaw condition did not cause changes in pH and rheological pattern; however, viscosity tended to decrease (p < 0.05).